Counter realignment political change in the northeastern United States - Reiter, Howard L. (Cambridge University Press, 2011)
"In Counter Realignment, Howard L. Reiter and Jeffrey M. Stonecash analyze data from the early 1900s to the early 2000s to explain how the Republican Party lost the northeastern United States as a region of electoral support. Although the story of how the 'Solid South' shifted from the Democratic to the Republican parties has received extensive consideration from political scientists, far less attention has been given to the erosion of support for Republicans in the Northeast. Reiter and Stonecash examine who the Republican Party lost as it repositioned itself, resulting in the shift of power in the Northeast from heavily Republican in 1900 to heavily Democratic in the 2000s"--